Virtual Microscopic Simulation (VMS) of Light-Wave to Enhance the Student’s Understanding Level - Wibowo, Firmanul Catur; Anggraini, Dewi; Delina , Mutia (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2022)
This study aims to develop a valid Virtual Microscopic Simulation (VMS) media used in light wave learning and evaluate the use of VMS media in increasing students’ level of understanding. The research method used in this research is research and development using the ADDIE model. The sample in this study consisted of 35 students at one of the universities in central Jakarta, Indonesia. The results showed that the development of VMS on the light wave material, when implemented, the gain test calculation increased the level of students’ understanding of 0.56 in the medium category. The results of the level of student understanding obtained complete understanding data by 52% of students understanding partly, 42% of students understanding incorrectly, and 3% of students not understanding. This shows that using VMS media on light wave material can enhance student understanding.